2014
DOI: 10.1103/physreva.90.053623
|View full text |Cite
|
Sign up to set email alerts
|

Realization of fractional Chern insulators in the thin-torus limit with ultracold bosons

Abstract: Topological states of interacting many-body systems are at the focus of current research due to the exotic properties of their elementary excitations. In this paper we suggest a realistic experimental setup for the realization of a simple version of such a phase. We show how ^-interacting bosons hopping on the links of a one-dimensional ladder can be used to simulate the thin-torus limit of the two-dimensional (2D) Hofstadter-Hubbard model at one-quarter magnetic flux per plaquette. Bosons can be confined to l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 77 publications
1
72
0
Order By: Relevance
“…For example, the Hofstadter Hamiltonian on a two-leg ladder can give rise to a topological phase provided an additional ad-hoc off-diagonal term is added [19], and similar topological phases are also predicted in the same ladder geometry when the arXiv:1708.02929v1 [cond-mat.quant-gas] 9 Aug 2017 magnetic flux per plaquette is spatial oscillating [20,21]. While these models go in the direction that one can have topological phases protected by the inversion symmetry by introducing a spatial modulation of the physical parameters [22][23][24][25], the phases discussed here represent, to the best of our knowledge, the first example of noninteracting topological states stabilized by the Hofstadter Hamiltonian in a ladder geometry with synthetic length L y > 2.…”
mentioning
confidence: 83%
“…For example, the Hofstadter Hamiltonian on a two-leg ladder can give rise to a topological phase provided an additional ad-hoc off-diagonal term is added [19], and similar topological phases are also predicted in the same ladder geometry when the arXiv:1708.02929v1 [cond-mat.quant-gas] 9 Aug 2017 magnetic flux per plaquette is spatial oscillating [20,21]. While these models go in the direction that one can have topological phases protected by the inversion symmetry by introducing a spatial modulation of the physical parameters [22][23][24][25], the phases discussed here represent, to the best of our knowledge, the first example of noninteracting topological states stabilized by the Hofstadter Hamiltonian in a ladder geometry with synthetic length L y > 2.…”
mentioning
confidence: 83%
“…There are three magnetic unit cells in the x direction and two magnetic unit cells in the y direction of the torus. In this low-dimensional realization, the ground state multiplet is composed of two charge density waves [42]. As θ y traverses [0,2π ), the energies of two quasidegenerate ground states are interchanged and return to their original values after θ y traverses another period from [2π,4π ) (see Fig.…”
Section: A Ground State Degeneracymentioning
confidence: 99%
“…It is known that the Laughlin state, which in two dimensions on a torus corresponds to a twofold degenerate ground state that cannot be resolved by local observables, becomes a pair of charge density waves in the thin torus geometry of Fig. 1(b) [41,42]. Using bosonization methods we characterize the bulk and the edge excitations of the precursor to the Laughlin state on a ladder.…”
Section: Introductionmentioning
confidence: 99%
“…They reported an observation of the chiral currents flowing around the ladder due to the effective magnetic field 1,7 . Motivated by this experimental ability, the coupled wire realization of the bosonic Laughling ν = 1/2 fractional quantum Hall effect (FQHE) introduced by Kane et al 8 , was recently suggested in two-leg ladders for strong on-site interactions 9,10 .…”
Section: Introductionmentioning
confidence: 99%